Implementation of Installation and Maintenance Portable Fire Extinguisher in Circuit Breaker Manufacture - Herdy Perdana Wicaksono (Universitas Airlangga, 2020)
Introduction: A portable fire extinguisher is one of the effective and active fire protection tool equipment used to extinguish fires at the beginning of a fire. The occurrence of a fire does not immediately become a big fire but it is starts from a small fire. This small fire is perfectly extinguished by using a portable fire extinguisher. Installation and maintenance of a portable fire extinguisher is one of the systems for fire prevention. However, it is important to know that a good and effective implementation must be balanced with proper installation and maintenance in accordance with existing regulations so that later it can function properly. This study aims to evaluate the application of the installation and maintenance of portable fire extinguishers at PT Y Indonesia. Methods: This research used descriptive research method with cross sectional approach. The data were obtained by observation using observation sheets and measurements directly in the field using a meter. Results: PT Y Indonesia has a policy regarding the installation and maintenance of APAR but its application has not fully met the requirements except for the color, pressure and distance between APAR. Conclusion: The implementation of APAR installation at PT Y Indonesia has not been in accordance with the relevant regulations except for APAR color, and the distance between APAR and implementation of maintenance is only done once a month without conducting detailed inspection with a period of 6 months and 12 months.Keywords: installation, maintenance, portable fire extinguisher